Penerapan Metode Cooperative Learning untuk Meningkatkan Hasil Belajar Renang Gaya Bebas - Sulikan Sulikan (IKIP Budi Utomo Malang, 2017)
Education is a conscious and planned effort to create an atmosphere of learning and learning process so that learners actively develop their potential to have spiritual, religious, self-control, personality, intelligence, noble character and skills needed by him, nation and state society (UU Sistem National Education article 1 paragraph 1). Education is organized as a process of lifelong learning of the students by giving exemplary, building the will and developing the creativity of learners in the learning process and developing the culture of reading, writing and arithmetic. The objective of the study was to improve the learning outcomes of Free Styles Swimming through the implementation of Cooperative Learning method. The problem in this research is “Whether the application of cooperative learning method can improve the learning result of Freestyle Swimming. The method of this research is class action research which involves repetitive reﬂection and consists of four stages: planning, action, observation and reﬂection. The subject of this research is Student Physical Education Health and Recreation IKIP Budi Utomo Malang force 2014 as many as 30 people. The result of the research shows that before the implementation of learning with cooperative learning method, the value of free class swimming lesson (Pre Cycle) is only equal to 16,67% with less category and in cycle I is implemented by applying cooperative learning method of learning result of freestyle pools = 63.33% with suffcient category and in cycle II which emphasize improvement in cycle I can be known implementation of cooperative learning method on free style swimming course increased and succeeded because able to reach = 93,33,00%. This is in accordance with the classical completeness criteria (KKM), which is 70%. In conclusion, the implementation of cooperative learning method can improve learning result of freestyle swimming at Student of Physical Education Health and Recreation IKIP Budi Utomo Malang Force 2014.